Gender differences in mobilization for collective action: case studies of villages in Northern Nigeria - Abdulwahid, Saratu (International Food Policy Research Institute, 2006)
Men and women participate in collective action for different purposes in northern Nigeria. Field work conducted in six villages show that while men engage in community activities such as road repairs, maintenance of schools and hospitals, refuse collection and maintenance of the traditional village government, women mobilize around activities such as savings, house and farm work and care giving. It is argued that men mobilize around community activities outside the home because of their public orientation and because they want to maintain their dominance of that space. Women, in contrast, mobilize around activities in keeping with their domestic orientation and traditional roles such as care giving and housework. Religion also influences the extent of women’s participation in collective action. Because men have command of community institutions, they are better able to access the resources embedded in these institutions, but women are able to negotiate within established social structures for better conditions. Given the socio-cultural characteristics of communities in northern Nigeria, an effective strategy for collective action is collaboration between men’s and women’s groups rather than separatism or integration.